Legal Review of the Licensing Process in the Field of Trade within the Sabang Free Trade and Free Port Zone - Hendra Setiawan; Azhari Yahya; Nurdin M. H. (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Law Number 37 of 2000 concerning the Enactment of Government Regulation in Lieu of Law Number 2 of 2000 on the Sabang Free Trade Zone and Free Port into Law designates Sabang as a Free Trade Zone and Free Port (FTZ). This area is legally separated from the customs territory, thereby exempting it from import duties, value-added tax, and luxury goods sales tax. The management of the zone is carried out through the Sabang Free Zone and Free Port Authority (BPKS). The establishment of the Sabang FTZ aims to stimulate economic growth, attract investment, and promote industrial and trade development in Aceh and Indonesia in general. However, in practice, the implementation of trade licensing procedures within the Sabang Free Trade and Free Port area has not been fully effective. This is mainly due to regulatory disharmony, including the reduction of delegated authority scope, which has created obstacles for business actors in conducting their activities locally and has resulted in insufficient legal certainty. This research is a normative legal study using statutory and conceptual approaches. The data were obtained from primary, secondary, and tertiary legal materials, supported by interviews with relevant informants. Data collection was conducted through library research and analyzed qualitatively. The findings indicate that the licensing process for import-related trade activities at the BPKS Sabang Port has not been optimal due to weak regulatory harmonization and poor synchronization of authority between BPKS as the zone authority and the central government. In addition, the licensing process is still burdened by multi-layered bureaucracy and uncoordinated inter-agency procedures. This study recommends that the government harmonize regulations to avoid overlapping authority with the Sabang Free Zone and Free Port Authority (BPKS). Furthermore, it is necessary to clarify institutional authority within statutory regulations, simplify the integrated licensing system, and conduct periodic regulatory evaluations to ensure legal certainty and improve administrative efficiency.